Lab tests can be used to predict phosphatidylethanolmeasured high-risk alcohol use among people with HIV: - Silva,C. Espinosa da; Scheffler.A; Fatch.R; Muyindike.W; Emenyonu N.I; J. Adong .J; Chamie .G; Ngabirano.G; Kekibiina.A; Tumwegamire.A; Marson.K; Beesiga.B; et al. (Alcohol and Alcoholism, 2025)
Background: Unhealthy alcohol use is prevalent among persons with HIV (PWH) and is associated with adverse outcomes, but is underestimated partly due to use of self-reported measures prone to underreporting. Phosphatidyl ethanol (PEth) is a direct measure of past month alcohol consumption but is costly. We assessed whether lab and health data representing alcohol-associated physiologic changes could be leveraged with machine learning to predict PEth-measured high-risk alcohol use among PWH. Methods: We pooled baseline data from two studies among PWH in Uganda that measured PEth (N = 988), and classified PEth as no/low/moderate (Peth)
a proof-of-concept using machine learning
Keywords: screening; detection; alcohol biomarkers; prediction tool